2022
DOI: 10.3390/cancers14071604
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation JK-206 Targets the Oncogenic Signal Mediator RHOA in Gastric Cancer

Abstract: Ras homologous A (RHOA), a signal mediator and a GTPase, is known to be associated with the progression of gastric cancer (GC), which is the fourth most common cause of death in the world. Previously, we designed pharmacologically optimized inhibitors against RHOA, including JK-136 and JK-139. Based on this previous work, we performed lead optimization and designed novel RHOA inhibitors for greater anti-GC potency. Two of these compounds, JK-206 and JK-312, could successfully inhibit the viability and migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…RHOA is a gene encoding for a member of the Rho family, a group of small GTPases with structural and signaling similarity to Ras proteins involved in the regulation of cytoskeletal dynamics, cell migration, and cell cycle, which has recently been identified as a promising therapeutic target in gastric cancer. 30 , 31 RHOA mutations have been described in gastric cancers, where they have been shown to be almost exclusively present in diffuse-type gastric carcinomas (14%-25%) 13 , 32 , 33 with the exception of a few intestinal-type/mixed-type gastric cancers (with anastomosing glands), 34 in appendiceal GCA, 35 and in some acute leukemias. 36 On the contrary, they seem to be extremely rare in colorectal adenocarcinoma (0.7%), as well as in other solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…RHOA is a gene encoding for a member of the Rho family, a group of small GTPases with structural and signaling similarity to Ras proteins involved in the regulation of cytoskeletal dynamics, cell migration, and cell cycle, which has recently been identified as a promising therapeutic target in gastric cancer. 30 , 31 RHOA mutations have been described in gastric cancers, where they have been shown to be almost exclusively present in diffuse-type gastric carcinomas (14%-25%) 13 , 32 , 33 with the exception of a few intestinal-type/mixed-type gastric cancers (with anastomosing glands), 34 in appendiceal GCA, 35 and in some acute leukemias. 36 On the contrary, they seem to be extremely rare in colorectal adenocarcinoma (0.7%), as well as in other solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The ras homologue family member A (RHOA) gene encodes a member of the Rho family of small GTPases 26 . When activated, it switches to an activated GTP‐bound form and promote actin cytoskeleton reorganization, which is associated with regulation of cell shape and multiple cellular functions 27,28 . RHOA has been demonstrated to be recurrently mutated in multiple types of cancer and played vital roles in the proliferation, migration and invasion of these tumour 29 .…”
Section: Discussionmentioning
confidence: 99%
“… 26 When activated, it switches to an activated GTP‐bound form and promote actin cytoskeleton reorganization, which is associated with regulation of cell shape and multiple cellular functions. 27 , 28 RHOA has been demonstrated to be recurrently mutated in multiple types of cancer and played vital roles in the proliferation, migration and invasion of these tumour. 29 RhoA has long been considered as an oncogene based on its mechanism of action by inducing RAS to transform into fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome indicated that shorter H-bond and salt bridge formation distances between the phosphates of L-HIPPO with highly basic residues led to the participation of a molecule in a narrower space, thus the acyl chains were also embedded in a narrower hydrophobic region compared to BH-1 and BH-2. On the contrary, the settlement of BH-1 and BH-2 in MA with greater H-bond and salt bridge formation distances of the inositol ring and basic residues also led to the increase of occupation of acyl chains in a larger hydrophobic space in MA, enhancing the binding affinity of BH-1 and BH-2 in MA [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. These findings encouraged us to create a large library containing 213 new L-HIPPO derivatives containing distinct aromatic groups.…”
Section: Discussionmentioning
confidence: 99%